Penguatan Ekonomi Sirkular Melalui Pendampingan Bank Sampah Produktif Pada Komunitas Ibu Pkk Desa Wisata Di Kabupaten Banyuwangi, Jawa Timur - umi faizah (Elsalima (Salam Institute), 2026)
Waste management challenges in tourism village areas of Banyuwangi Regency represent a strategic issue that directly intersects with environmental quality and sustainable tourism competitiveness. The PKK (Family Welfare Empowerment) women's community, as the frontline of social empowerment at the village level, lacks adequate capacity to integrate circular economy practices into community-based waste management systems. This community service program aims to (1) implement productive waste bank mentoring based on circular economy principles for PKK women's communities in Banyuwangi's tourism villages, and (2) measure the program's impact on environmental awareness and community economic value. The program was conducted on November 24, 2025, involving 50 active participants using a Participatory Action Research (PAR) approach. Activity stages included participatory assessment, collaborative planning, productive waste bank implementation, monitoring, and critical reflection. Evaluation was conducted using Kirkpatrick's Four Levels of Evaluation framework integrated with Bloom's Taxonomy. Results showed significant improvements across all competency aspects: the cognitive domain increased from an average of 48.2% to 84.6% (Good category), the affective domain from 52.4% to 87.3% (Excellent category), and the psychomotor domain from 45.6% to 82.1% (Good category). The program successfully fostered an organized productive waste bank system, increased community supplementary income averaging IDR 350,000–500,000 per month per group, and cultivated sustainable ecological awareness. These findings demonstrate that integrating the PAR approach with circular economy models can holistically and sustainably transform community capacity within tourism village contexts.